RANCANG BANGUN SISTEM INFORMASI KEPEGAWAIAN DI SMA NEGERI 1 ENDE - Senhora Embu, Maria Cova Da Iria (JURSIMA, 2022)
SMA Negeri 1 Ende is one of the State Senior High Schools in the city of Ende, Ende Regency and is the leading school as well as the most favorite school. So far, the use of technology has not been left behind by other schools, but only limited to typing and making reports without using a special system in its management so that data accumulation and even loss often occur. This research was conducted with the aim that the resulting data and information would be faster, easier and more accurate because it no longer uses conventional methods but is computerized so that when data is needed it no longer takes a long time to search. Information can be thought of as data that is processed into a meaningful form which can then be processed into a decision. This study uses a type of qualitative research, which is carried out using data collection methods, namely documentation, observation, structured interviews. The system used for the design of the Employee Information System at SMA Negeri 1 Ende uses DFD (Data Flow Diagram) and the software design method used is the waterfall method. While the programming language used in this study is the PHP and MySQL programming languages, then for testing this system using the BlackBox method. From this research resulted in an Employee Information System Design at SMA Negeri 1 Ende which can facilitate administration in the process of managing employee data such as SK data, Diploma data, Certificate Data and Deed Data. Keywords: Design, Information Systems, Management, Data, Employees. Keywords: System, E-commerce, Waterfall, Black Box Testing, UMKM.